Strong synergetic effect of fibril-like nucleator and shear flow on the melt crystallization of poly(l-lactide). (February 2017) - Ma, Piming; Yu, Qingqing; Shen, Tianfeng; Dong, Weifu; Chen, Mingqing
Graphical abstract: Highlights: Synergetic effect of OXA and shear flow on the crystallization of PLLA is created. The high-temperature crystallization of PLLA is considerably enhanced. The morphology evolution and crystallization mechanism are revealed. Abstract: Bio-based and bio-degradable poly(l -lactide), PLLA, suffers from low crystallization rate. The synergetic effect of fibril-like nucleator (N 1, N 1′ -(ethane-1, 2-diyl)bis(N 2 -phenyloxalamide)) (OXA) and shear flow on speeding up the melt crystallization of the PLLA is the first time reported in this work. The synergetic effect was investigated by using a rheometer. Neither fibril-like OXA nor shear flow showed obvious accelerating effect at 155 °C on the crystallization of PLLA leading to limited crystallinity ( Xc ) within 70–100 min. In contrast, a crystallinity of more than 40% and an onset crystallization time ( tonset ) of less than 3 min were achieved by tailoring the shear conditions. The critical shear condition for the fast crystallization of the PLLA/OXA systems at 155 °C is 0.4 rad/s for 10–15 s. A lower shear temperature (e.g., 150 °C in comparison with 155 °C) would increase the crystallization rate much further. Mechanism study revealed that the OXA fibril network and a certain extent of PLLA chain orientation that induced by the shear flow while subsequently stabilized by the OXA fibrils are responsible for the significantly enhanced nucleation and overall melt crystallization kinetics. In addition, the shear flow and fibril-like OXA nucleators not only facilitated the crystallization of PLLA α -form crystals but also promoted the formation of α ′- (or δ ) and β -form crystals.